Effects of driver compensatory behaviour on risks of critical pedestrian collisions under simulated visual field defects. - Jieun Lee; Makoto Itoh (PLoS ONE, 2020)
Compensatory behaviour is regarded as a helpful strategy to mediate drivers' deteriorated hazard perception ability due to visual field defects. However, helpfulness of compensatory behaviour for drivers with advanced visual field defects has largely unexplored. This study aims to clarify the effectiveness and limitation of compensatory head movements in critical situations where included pedestrians stepping off a sidewalk under the simulation of advanced visual defects. 18 healthy-sighted drivers participated the data collection that was conducted in a driving simulator under three driving conditions: (1) without visual impairment, (2) with visual impairment and not performing active compensation, and (3) with visual impairment but performing active compensation. The result showed that active compensation led quick accelerator and brake response times, reducing the risk and number of pedestrian collisions. The active compensation led a decrease in the number of non-responses to hazardous pedestrians compared to while driving not performing compensation. However, the compensation could not reduce the number of pedestrian collisions to those of healthy-sighted drivers. Compensatory viewing behaviour contributed to improved driving performance as well as has limits to lead driving performance like healthy-sighted drivers. Developing driver assistance systems and practical compensatory strategies concerning the degrees of impairment and traffic conditions may provide opportunities to improve driving safety deteriorated hazard perception for visually impaired drivers.